PENGARUH PAPARAN RADIASI GELOMBANG ELEKTROMAGNETIK EXTREMELY LOW FREQUENCY (ELF) TERHADAP KESEHATAN OTAK - Haikal Oke Wicaksono; Sudarti, Yushardi (CV. Adiba Aisha Amira, 2024)
Extremely Low Frequency (ELF) electromagnetic waves are produced by several electrical devices (0-300Hz). This causes quite negative effects on human health. The aim of this research is to analyze the effects of ELF exposure on brain health. The method used in this research is a review with valid and relevant sources from several books and journals, with. The search was carried out using keywords related to ELF, exposure, and brain. From several literature results from research showing human brain disorders, measurements carried out for 30-60 minutes at an intensity of 50Hz have no effect on DNA damage. However, research on brain abnormalities in mice was carried out at intensities of 150μT, 300μT, 450μT. Exposure to an ELF field affects the brains of mice (white rats) at the intensity of the radiation, which is characterized by a decrease in brain function. Other studies show that exposure to ELF also causes headaches and dizziness and increases the risk of brain cancer and reproductive problems (but the results of this study are still not conclusive).